2022
DOI: 10.1016/j.jns.2022.120155
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination in patients with multiple sclerosis: Safety and humoral efficacy of the third booster dose

Abstract: Background As immunity against SARS-COV-2 wanes following first and second doses of vaccination, a third dose is administered in several countries around the world. Similarly to the first doses, risks related to vaccination and humoral immune response in patients with multiple sclerosis (MS) need to be assessed. Objective Characterize safety and humoral immune response following the third dose of COVID-19 vaccination in a large cohort of MS patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
69
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 11 publications
14
69
1
1
Order By: Relevance
“…However, they efficiently eliminate the infection probably due to a preserved functionality of innate and T cells response ( Giovannoni et al., 2021 ). Overall, the results reported in this study confirmed that cladribine treatment does not compromise the development of a specific humoral response, as previously observed ( Achiron et al., 2021b ; Dreyer-Alster et al., 2022 ); for ocrelizumab and fingolimod, a significant Ab response can be achieved with further vaccinations. Studies in larger cohorts, together with B and T cell-mediated responses profiling, will be needed to better clarify the effect of vaccination booster in pwMS in relation to their DMT and for any future vaccination campaign.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, they efficiently eliminate the infection probably due to a preserved functionality of innate and T cells response ( Giovannoni et al., 2021 ). Overall, the results reported in this study confirmed that cladribine treatment does not compromise the development of a specific humoral response, as previously observed ( Achiron et al., 2021b ; Dreyer-Alster et al., 2022 ); for ocrelizumab and fingolimod, a significant Ab response can be achieved with further vaccinations. Studies in larger cohorts, together with B and T cell-mediated responses profiling, will be needed to better clarify the effect of vaccination booster in pwMS in relation to their DMT and for any future vaccination campaign.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the low Ab response following vaccination, discontinuation of highly effective DMTs has not been recommended due to the high risk of relapse ( Giovannoni et al., 2021 ) and a booster dose was recommended. To date, data on booster have shown an adequate safety profile with a comparable adverse event incidence between the first vaccination cycle and booster ( Dreyer-Alster et al., 2022 ). IgG levels increase after booster in untreated and treated patients ( Dreyer-Alster et al., 2022 ), but data on B-depleting therapies and S1P modulators are not currently available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In individuals with MS, a relapse can be triggered by SARS-CoV-2 infection and vaccination 27,28 . In a cohort of 211 individuals with MS, the third dose of the BNT162b2 mRNA vaccine was associated with a transient increase of MS symptoms in 3.8% and a relapse in 3.3% 29 . Increased mortality and reduced efficacy of vaccination in MS are related to anti-CD20 therapies that reduce the B -cell count and can cause hypogammaglobulinemia 26,29 .…”
Section: Autoimmunementioning
confidence: 99%
“…27,28 In a cohort of 211 individuals with MS, the third dose of the BNT162b2 mRNA vaccine was associated with a transient increase of MS symptoms in 3.8% and a relapse in 3.3%. 29 Increased mortality and reduced efficacy of vaccination in MS are related to anti-CD20 therapies that reduce the B-cell count and can cause hypogammaglobulinemia. 26,29 The IRR for an acute demyelinating event is higher in the 28 days following 2 1.…”
Section: Autoimmune Demyelinationmentioning
confidence: 99%